2009
DOI: 10.1074/jbc.m109.051532
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Celastrol to Inhibit Hsp90 and Cdc37 Interaction

Abstract: The molecular chaperone heat shock protein 90 (Hsp90) is required for the stabilization and conformational maturation of various oncogenic proteins in cancer. The loading of protein kinases to Hsp90 is actively mediated by the cochaperone Cdc37. The crucial role of the Hsp90-Cdc37 complex has made it an exciting target for cancer treatment. In this study, we characterize Hsp90 and Cdc37 interaction and drug disruption using a reconstituted protein system. The GST pull-down assay and ELISA assay show that Cdc37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
154
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(171 citation statements)
references
References 76 publications
15
154
2
Order By: Relevance
“…HSP90 is an essential molecular chaperone that is involved in the post-translational folding and stability of a host of proteins that are important to the cancer cells, such as EGFR, cRAF, Akt, Met, HIF-1α, and telomerase (28). Zhang et al have reported that celastrol disrupts the association of HSP90 with co-chaperones p23 and cdc37 and allosterically regulates HSP90 chaperone activity by modifying its c-terminus, resulting in the degradation of HSP90 client proteins (29). Furthermore, we found that celastrol did not cause a major change in HSP90 protein levels in agreement with previous observations (10).…”
Section: Discussionsupporting
confidence: 93%
“…HSP90 is an essential molecular chaperone that is involved in the post-translational folding and stability of a host of proteins that are important to the cancer cells, such as EGFR, cRAF, Akt, Met, HIF-1α, and telomerase (28). Zhang et al have reported that celastrol disrupts the association of HSP90 with co-chaperones p23 and cdc37 and allosterically regulates HSP90 chaperone activity by modifying its c-terminus, resulting in the degradation of HSP90 client proteins (29). Furthermore, we found that celastrol did not cause a major change in HSP90 protein levels in agreement with previous observations (10).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, celastrol has been found to be a novel Hsp90 inhibitor (35,36). However, no study has found that the celastrol-induced apoptosis of myeloma cells was induced by Hsp90 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Celastrol has been reported to possess antioxidative activities and interfere with the interaction between HSP90 and CDC37. 33,34 Also, downmodulation of HSP90 potentially increase AAV transduction through the interaction with FKBP52 to increase AAV second-strand synthesis. 35 However, the HSP90 protein levels were not significantly different in 3T3-L1 preadipocytes with and without celastrol as determined by western blot shown in Supplementary Figure 3a.…”
Section: Discussionmentioning
confidence: 99%